Two-track-reflector-filters for CDMA mobile telephones - Bergmann, Andreas; Machui, Jürgen; Wagner, Karl Christian; Weigel, Robert (IEEE International Ultrasonics Symposium (IUS), 1996)
IF-filters for channel selection in mobile phones based on a CDMA system must offer very steep skirts as well as excellent phase linearity and small amplitude ripple within the passband. To fulfill all these requirements a conventional transversal surface acoustic wave (SAW) filter needs a large chip size. In order to reduce the total chip length we folded the propagation path of the SAW taking advantage of the reflector filter technique. Therefore, the usable time window for weighting becomes almost twice as large. We employed weighted reflectors not only to reflect the SAW but also to shape the filter frequency response. Thus we have more flexibility to design the transducers. We can make them shorter but still have lower impedances on quartz than with an unweighted reflector design. With this technique, we built filters at a center frequency of 110 MHz with an insertion attenuation of less than 15 dB, a 5 dB bandwidth of 1.26 MHz and an attenuation of more than 30 dB outside of a 1.80 MHz band. The chip is mounted in a 15.6×6.8 mm2 SMD package. The reflector filter fulfills the frequency response specification required for CDMA mobile telephones on a chip length reduced by about 4 mm compared with the transversal or SPUDT design technique
elib2cris::1512001600,bergmann1996